2000
DOI: 10.1155/s1110662x00000040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromophore interaction in photophysics and photochemistry of cyanine dyes

Abstract: Spectral and fluorescent properties of ketocyanine dyes (polyenic bis-ω,ω′-aminoketones) and cation-anionic polymethine dyes of various structures were studied. The symmetric ketocyanines were shown to have a long-wavelength absorption band bathochromically shifted in comparison with that of the asymmetric ketocyanines with the same total length of the polyenic chain. The nonlinear ketocyanines exhibit the additional short-wavelength band in their absorption spectra, which can be more intense than the longwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…As mentioned above, the S-S absorption spectra of dye 6 consist of two bands: an intense short-wavelength band and a much less intense long-wavelength band ( Figure 1 The positions of these bands, their intensity ratio, and the energy splitting (∆ν) between the S 1 and S 2 levels were explained in terms of interaction of two aminopolyenic chromophores in the dye molecule. The chromophores composing the dye (halves of dye 6 from the NMe 2 fragment to the carbonyl group) are oriented at an acute angle with respect to each other [2][3][4]. We found that the replacement of the O atom in the pyranone ring of ketocyanine 6 by the NMe group (dye 1) led to a dramatic change in the absorption spectrum of the dye (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, the S-S absorption spectra of dye 6 consist of two bands: an intense short-wavelength band and a much less intense long-wavelength band ( Figure 1 The positions of these bands, their intensity ratio, and the energy splitting (∆ν) between the S 1 and S 2 levels were explained in terms of interaction of two aminopolyenic chromophores in the dye molecule. The chromophores composing the dye (halves of dye 6 from the NMe 2 fragment to the carbonyl group) are oriented at an acute angle with respect to each other [2][3][4]. We found that the replacement of the O atom in the pyranone ring of ketocyanine 6 by the NMe group (dye 1) led to a dramatic change in the absorption spectrum of the dye (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Due to simple structures, these compounds appeared to be convenient for modeling various photophysical and photochemical processes. Recently we have studied the photonics of a number of ketocyanines, both simple and having a central pyranone fragment [1][2][3][4]. Their spectral and photophysical properties can be well explained in terms of the theory of chromophore interaction based on dipole-dipole interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have earlier 1-5 studied a series of the ketocyanine dyes (polyenic ω,ω´ bisamino ketones) with the central pyranone or pyridone moiety (1,2) and the polymethine salts corresponding to these dyes (3,4).…”
mentioning
confidence: 99%
“…6,7 Based on the concepts of the theory of chromophore in teraction and the experimental ratio of intensities of the long and short wavelength bands, we assumed that mol ecules 1 and 3 exist in the nonlinear conformation (1´ and 3´, respectively) in which the chromophores (polyene chains extending between the NMe 2 and carbo nyl groups) of the dyes are arranged at an acute angle to each other. [1][2][3] The question about the predominant conformation of compounds 2 and 4 remains unanswered, because their absorption spectra consist of a broad poorly re solved band.…”
mentioning
confidence: 99%